Spontaneous closure of an acquired ventricular septal defect. Issue 921 (1st July 2002) - Williams, R I; Ramsey, M W
Abstract : Ventricular septal defect (VSD) is a rare but serious complication of acute myocardial infarction requiring early surgical intervention. A patient with acquired VSD that spontaneously closed over three months is presented. The literature on spontaneous closure of acquired VSDs is also reviewed.